2018
DOI: 10.1093/ijnp/pyy031
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing Reveals Candidate NF-κB Target Genes Involved in Repeated Cocaine Administration

Abstract: BackgroundDrug-induced alterations in gene expression play an important role in the development of addictive behavior. Numerous transcription factors have been implicated in mediating the gene expression changes that occur in drug addiction. Nuclear factor kappa B is an inducible transcription factor complex that is rapidly activated by diverse stimuli.MethodsWe performed next-generation high-throughput sequencing of the prefrontal cortex in a mouse model of repeated cocaine administration combined with pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…It showed that except Acyp2 gene, Cacna2d3, Epha6, Nedd4l and Vav2 were down‐regulated by MET via piRNA when induced by cocaine. And as for pathways these genes located such as mmu04024: cAMP signaling pathway, mmu04010: MAPK signaling pathway, mmu04360: Axon guidance and so on were reported related to drug dependence (Hope et al., 2007; Y. Wang et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…It showed that except Acyp2 gene, Cacna2d3, Epha6, Nedd4l and Vav2 were down‐regulated by MET via piRNA when induced by cocaine. And as for pathways these genes located such as mmu04024: cAMP signaling pathway, mmu04010: MAPK signaling pathway, mmu04360: Axon guidance and so on were reported related to drug dependence (Hope et al., 2007; Y. Wang et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The socioeconomic challenges faced by people with addiction problems are complex and have significant consequences both for those affected and for society as a whole. Addiction, whether related to substances such as drugs and alcohol, activities such as gambling, or behaviors such as Internet or smartphone use, is considered a major public health problem with significant socioeconomic implications [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The impact of addiction on an individual’s socioeconomic status manifests itself in various facets and includes economic hardship, homelessness, and incarceration [ 42 , 44 , 48 ].…”
Section: Socioeconomic Associations Between Psychiatric Illness and C...mentioning
confidence: 99%
“…The socioeconomic burden of addiction goes beyond the individual impact and extends to broader societal structures. For example, addiction causes significant damage to the health and socioeconomic positions of those affected, leading to additional burdens on society [ 43 , 47 ]. Furthermore, addiction is associated with increased healthcare costs, increased hospitalization, and unfavorable clinical outcomes, contributing to the overall socioeconomic impact [ 51 ].…”
Section: Socioeconomic Associations Between Psychiatric Illness and C...mentioning
confidence: 99%
“…Chronic or repeated exposure to cocaine causes alterations in numerous genes in various regions of the brain in animal models 11,12 . In transcriptome profile analysis of the prefrontal cortex after repeated cocaine administration in mice, changes were identified in genes related to the MAPK signal pathway and NFκB target genes 13,14 . Some researchers have investigated the molecular effects of heroin addiction in animal models and human studies using microarrays 15‐17 .…”
Section: Introductionmentioning
confidence: 99%